Rewriting histories of the use of force : the narrative of 'indifference' - Verdebout, Agatha, 1987- (Cambridge : Cambridge University Press, 2021)
It is commonly taught that the prohibition of the use of force is an achievement of the twentieth century and that beforehand States were free to resort to the arms as they pleased. International law, the story goes, was 'indifferent' to the use of force. 'Reality' as it stems from historical sources, however, appears much more complex. Using tools of history, sociology, anthropology and social psychology, this monograph offers new insights into the history of the prohibition of the use of force in international law. Conducting in-depth analysis of nineteenth century doctrine and State practice, it paves the way for an alternative narrative on the prohibition of force, and seeks to understand the origins of international law's traditional account. In so doing, it also provides a more general reflection on how the discipline writes, rewrites and chooses to remember its own history.
Introduction. Aim, methodology and outline -- The 'use of force' in the nineteenth century : some conceptual clarifications -- The use of force in writings of 'naturalist' inclination -- The use of force in writings of 'eclectic' inclination -- The use of force in writings of 'positivistic' inclination -- Justifying the use of force in the 'centre' -- Justifying the use of force in the 'semi-peripheries' -- Justifying the Use of Force in the 'Peripheries' -- Disciplinary Beliefs about International Law and the Narrative of Indifference : a Mirror-Effect -- The emergence of the narrative of indifference in the interwar : preserving identity by restoring credibility.
Title from publisher's bibliographic system (viewed on 14 Sep 2021).
Keywords: Intervention (International law) -- History